2010
DOI: 10.1111/j.1533-2500.2009.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Changes in Migraine Patients before, during and after Migraine Attacks

Abstract: Migraine attacks are characterized by headaches associated with neurological, gastrointestinal, and autonomic symptoms. A relationship between migraine and hypertension or hypotension is controversial. In this study, we aimed to determine if blood pressure changes were related to migraine attacks. From the outpatient clinic of our neurology department, 62 normotensive migraine patients with and without aura were chosen for study in accordance with the International Headache Society 2004 criteria. A questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Figure 1 additionally shows that strong platelet aggregation was accompanied by a marked decline in mean aortic pressure. This decline was prevented by clopidogrel 9 or L‐NMA 8 and reminds to the diastolic hypotension (pressure below 60 mmHg) observed in a number of patients during migraine attacks 66 . It is conceivable that the hypotension in migraine contributes to, or may be part of, the autonomic dysfunction that causes nausea and emesis.…”
Section: Role Of 5‐ht No and Prostaglandin Formation In Our Rat Modelmentioning
confidence: 83%
See 1 more Smart Citation
“…Figure 1 additionally shows that strong platelet aggregation was accompanied by a marked decline in mean aortic pressure. This decline was prevented by clopidogrel 9 or L‐NMA 8 and reminds to the diastolic hypotension (pressure below 60 mmHg) observed in a number of patients during migraine attacks 66 . It is conceivable that the hypotension in migraine contributes to, or may be part of, the autonomic dysfunction that causes nausea and emesis.…”
Section: Role Of 5‐ht No and Prostaglandin Formation In Our Rat Modelmentioning
confidence: 83%
“…This decline was prevented by clopidogrel 9 or L-NMA 8 and reminds to the diastolic hypotension (pressure below 60 mmHg) observed in a number of patients during migraine attacks. 66 It is conceivable that the hypotension in migraine contributes to, or may be part of, the autonomic dysfunction that causes nausea and emesis. Such dysfunction might result from increased plasma levels of serotonin that stimulate 5-HT3 receptors on the parasympathetic nuclei in the area postrema, located outside the blood-brain barrier.An increase of vagal motor activity will, on its turn, stimulate release of serotonin from enterochromaffin cells, further exciting vagal activity in a positive serotonergic-parasympathetic feedback loop.…”
Section: Role Of 5-ht No and Prostaglandin Formation In Our Rat Modelmentioning
confidence: 99%
“…However, other studies have associated systolic hypertension with chronic daily headache (Gipponi et al, 2010) and chronic migraine (Bigal et al, 2002; Barbanti et al, 2010), but not episodic migraine or tension-type headache in non-pregnant adult patients. Diastolic hypertension has been associated with increased frequency of episodic migraine in one study (Gudmundsson et al, 2006) but diastolic hypotension was non-significantly associated with migraine in another study (Seçil et al, 2010). Some have suggested that autonomic dysfunction is an important part of migraine; many migraineurs exhibit symptoms, such as diarrhea or sweating, of parasympathetic over-activity (Melek et al, 2007).…”
Section: Systemic Blood Pressure and Migrainementioning
confidence: 99%
“…Therefore, patients with an increase in neuronal excitability due to low CSF Mg 2ϩ levels are more susceptible to migraine attacks. Moreover, patients suffering from migraine are often hypotensive during attacks (462), which can be explained by increased NO levels. NO is an important vasodilator and modulator of brain blood flow (376).…”
Section: Migrainementioning
confidence: 99%